Continuity Amid Commercial Buildings in Yeonnam-dong, Seoul - Jae-Young Lee (Buildings)
This study tracks changes in commercial buildings in Yeonnam-dong that have undergone commercial transformation, examining these shifts within the context of urban organization and their relationships with economic and socio-cultural flows. It also analyzes the architectural elements that reflect the placeness characteristics of an area. On-site surveys were conducted to assess the continuity and discontinuity in the characteristics of 62 renovated and 40 newly constructed buildings. Additionally, shifts in social perceptions regarding physical changes were explored through an analysis of commercial districts and interviews with visitors, store owners, and architects. Yeonnam-dong has a distinct physical environment, as well as economic, social, and cultural characteristics that distinguish it from mainstream areas, such as large apartment complexes and typical commercial zones. The area, with its winding alleyways from the pre-modern period and low-rise housing—marginalized from large-scale development—evoked nostalgia and created a distinctive sense of authenticity or placeness, which was further enhanced by the presence of exotic restaurants, cafés, ateliers, and creative activities of early gentrifiers. However, rapid commercialization has led to the displacement of these early gentrifiers, an influx of new investments and construction, and shifts in commercial flows. Consequently, the area’s authenticity has become diluted, and visitors’ perceptions of it have changed. Despite this, architectural elements observed in renovated buildings are preserved and incorporated into newly constructed ones. Features such as semi-basements, exterior straight stairs, and brick façades continue to reflect the locality. Detached and multi-household homes from the 1960s to the 1990s have evolved into a new hybrid commercial–residential form designed for commercial purposes. This is a response to small plot sizes in Korean residential areas and reflects the current economic and cultural demands of commercial gentrification. The urban and architectural characteristics of this area are not only a unique physical environment but also hold socio-cultural significance as ordinary heritage. Therefore, this study proposes institutional measures to preserve urban and architectural continuity while controlling the ongoing commercialization.